PERANCANGAN ULANG (REDESIGN) TEMPAT TIDUR UNTUK LANSIA DENGAN METODE KANSEI ENGINEERING DAN PENDEKATAN GERONTOLOGY - Rachmad Hidayat (JURNAL TEKNIK INDUSTRI, 2017)
In this research, conducted observations of everyday activities that seniors do in bed. Basically the use of bed rest is used for the elderly, but some seniors also do activities such as eating, embroidery, and others. Bed conditions that exist today are pretty good, but when used by older people often occurs difficulties. Difficulties experienced by older adults when using the position of the bed go to bed by 40% this was due to the high bed, a sitting after lying down as much as 33% this is because the elderly are still using hand and elbow as a support and positioning out of bed by 27%. A. Therefore done to improve the design of the old and new designs in accordance with user expectations for improved attributes in terms of functions and needs of seniors as follows bed frame, headboards, tools to build and support needs (table). Improvements made in order to accommodate all activities with emphasis on the elderly in terms of ergonomics and comfort in its use